2022
DOI: 10.1101/2022.10.31.22281164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing Prescribing in Older Adults with Multimorbidity and Polypharmacy in Primary Care: A Cluster Randomized Clinical Trial (OPTICA Trial)

Abstract: ImportanceInappropriate prescribing and prescribing omissions are major drivers of healthcare-related harm. Medication review may help improve pharmacotherapy.ObjectiveTo study the effects of a primary care medication review intervention centered around an electronic clinical decision support system (eCDSS) on medication appropriateness and the number of prescribing omissions in older adults with multimorbidity and polypharmacy compared to usual care.Design and SettingThe “Optimising PharmacoTherapy In the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The methods and results of the ‘Optimising PharmacoTherapy In the multimorbid elderly in primary Care’ (OPTICA) trial have been reported elsewhere 18–20. In brief, 323 patients from 43 GP practices were recruited into this cluster randomised clinical trial between January 2019 and February 2020.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods and results of the ‘Optimising PharmacoTherapy In the multimorbid elderly in primary Care’ (OPTICA) trial have been reported elsewhere 18–20. In brief, 323 patients from 43 GP practices were recruited into this cluster randomised clinical trial between January 2019 and February 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Table 6 shows the association between patients' attitudes towards deprescribing and the implementation of prescribing recommendations that were generated as part of the OPTICA medication review intervention (n=31). On average, one prescribing recommendation to stop or start a medication were reported to be implemented per Open access patient (reported elsewhere 35 ) and 59% of patients in the intervention group had one or more prescribing recommendation implemented. We did not find any evidence for a statistically significant association between patients' attitudes towards deprescribing and the implementation of deprescribing recommendations.…”
Section: Implementation Of Prescribing Recommendationsmentioning
confidence: 99%
“…The protocol of the OPTICA trial was published previously 27. We conducted a cluster randomised controlled trial with 43 general practitioners as clusters 28. The trial was conducted from 2018 to 2021.…”
Section: Methodsmentioning
confidence: 99%
“…The methods and results of the 'Optimising PharmacoTherapy In the multimorbid elderly in primary Care' (OPTICA) trial (clinicaltrials.gov identifier: NCT03724539) have been reported elsewhere. [17][18][19][20] From January 2019 to February 2020, a total of 323 patients from 43 GP practices were recruited into this cluster randomized clinical trial. The last patient completed the 12-month follow-up in February 2021.…”
Section: Overview Of the Optica Trialmentioning
confidence: 99%